Menjaga Kemudahan Berbisnis Melalui Pinjaman Perbankan dan Transformasi Digital terhadap Produktivitas Kelapa Sawit di Provinsi Lampung: Pendekatan Polinomial - Moh Najikhul Fajri; Achmad Kharisudin (Research and Development Agency Ministry of Home Affairs, 2025)
This study analyses the complementary effects of bank financing and digital transformation on palm oil productivity in the Lampung Province. This study used secondary panel data from 15 districts and cities in Lampung from 2014 to 2022. This study applies spatial efficiency analysis in the form of slack-based measurement and data envelopment analysis to measure the amount of productivity. Meanwhile, the effect of banking financing and digital transformation on productivity uses an advanced polynomial static panel regression, generalized least squares. The results show that banking credit in the agricultural sector has a significant positive effect, and digitalization has a U-shaped characteristic (Kuznet’s U-shaped curve) that leads to a positive effect on palm oil productivity under certain conditions. Bank credit acts as a medium-term funding stimulus, so the scale of the palm oil business is relatively maintained. In line with this, it needs to be accompanied by technological capacity and support in the form of internalization, both structurally and functionally, so that the efficiency of palm oil production can be navigated properly. Therefore, the government and institutions must expand digital access across Lampung to surpass the critical threshold and improve farmers’ digital skills. At the same time, basic access, such as subsidized fertilizers and the development of agricultural platforms, is essential given the substantial future potential of digitalization. Financial institutions must also evaluate and simplify credit access with sufficient guarantees and provide interest subsidies (through interbank and local government collaboration) to accommodate potential productivity gains. In terms of regional living standards, promoting job creation across sectors could be beneficial. Meanwhile, to mitigate the adverse effects of industrialization on palm oil productivity, a synergistic partnership system between farmers and industries with fair pricing is necessary to ensure a broader supply and sustained production growth.